2016
DOI: 10.1155/2016/6295817
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hematoma after Thoracolumbar Posterior Fusion Surgery without Decompression for Thoracic Vertebral Fracture

Abstract: We present a rare case of spinal epidural hematoma (SEH) after thoracolumbar posterior fusion without decompression surgery for a thoracic vertebral fracture. A 42-year-old man was hospitalized for a thoracic vertebral fracture caused by being sandwiched against his back on broken concrete block. Computed tomography revealed a T12 dislocation fracture of AO type B2, multiple bilateral rib fractures, and a right hemopneumothorax. Four days after the injury, in order to promote early orthostasis and to improve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Although occurrences of postoperative spinal hematoma formation requiring emergency surgery are rare, it is nevertheless important to control perioperative bleeding to decrease its incidence. [ 7 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although occurrences of postoperative spinal hematoma formation requiring emergency surgery are rare, it is nevertheless important to control perioperative bleeding to decrease its incidence. [ 7 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of acute spinal epidural hematoma, as described in the medical literature, are sudden onset of severe pain along the spinal column lasting from a few minutes to a few hours, possibly with focal or evolving neurological symptoms such as flaccid paralysis or loss of sphincter control. [1417] Occasionally, there is transient improvement in the neurology. [8] Thus, acute spinal pain in a patient on anticoagulants should raise the suspicion of spinal epidural hematoma even before any neurological symptoms appear.…”
Section: Discussionmentioning
confidence: 99%
“…[2,6,17] Major predisposing factors for pSEH included; perioperative/postoperative coagulation disorders, multilevel spinal surgery, prior spine surgery, and intraoperative cerebrospinal fluid leaks (CSF) [Tables 1 and 3]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The times to onset of symptomatic postoperative pSEH following all-level spine surgery ranged from an average of 2.7 postoperative hours, [1] to less than 24, [2] to between 24-48 postoperative hrs. [5] [Tables 1-4].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The most critical factors to limit/avert permanent neurological sequelae of pSEH included; early recognition of new postoperative neurological deficits, obtaining immediate magnetic resonance imaging (MR) studies, and performing emergency spine surgery where indicated [Tables 1-4]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Incidence of pSEH e incidence of symptomatic postoperative spinal epidural hematomas (pSEH) involving all spinal levels ranged in 7 studies from 0.1% to 1%, [1,2,4,8,9,15,16] in 5 series from <1% to 2.9%, [11,12,15,17,18] and in 3 series between 3%-4.46% (i.e., the 1 of 10 patients with a 10% incidence of pSEH was considered an outlier) [2,6,17] [Tables 1 and 2]. [1][2][3][4][5][6][7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%